Visual forms and placement of carved components in traditional timber houses of Kelantan and Terengganu - Said, Ismail; Kamaruddin, Zumahiran (2010)
This paper presents an analytical study of the visual forms and placement of carved components in the timber houses of Kelantan and Terengganu which reflects its significant attributes and uses. An analytical study on ten houses in Kelantan and five houses in Terengganu was conducted by visual descriptive and interpretative analyses on 15 sets of reports and carving measured drawings of the houses. Data from the drawings was triangulated and validated with interpretations from the prominent woodcarvers on art and crafts of woodcarving, and supported by literatures of Malay woodcarving. The analysis revealed that several types of carved components with distinctive features including wall, door and window ventilation panels, railings, roof gable end and gate panels were fitted in harmonious relationship with the architectural components within the house fabrics. The placement of these components with specific carving motif, shape, size and layout in the houses reflects certain orders and regional identity of the Kelantan and Terengganu traditional houses.